Sterile neutrinos in light of the Cabibbo-angle anomaly. Issue 1 (1st February 2023) - Kitahara, Teppei; Tobioka, Kohsaku
Abstract: Based on recent developments in the lattice simulations and calculations of the radiative corrections to the charged-current interactions, the uncertainties for each component in the CKM matrix have been sophisticated. It is known that the first-row CKM unitarity is violated at about 3 σ level, implying a 3 σ level deviation from the standard model prediction. This new deviation is called Cabibbo-Angle Anomaly (CAA). These CKM components are mainly extracted from kaon, pion, and the superallowed beta decays. In this contribution, we point out that a MeV scale sterile neutrino can economically explain the CAA. We consistently investigate the sterile neutrino contributions to the kaon, pion, superallowed beta decays, and also the Fermi coupling constant.